Rethinking public space: A new lexicon for design - Edward Robbins (Urbani Izziv, 2008)
In the debate about the importance and the design of well planned public open spaces, it is critical that we address the meaning and implications of the notions of public space. Most definitions are fundamentally overdetermined and fraught with contradictions and ambiguities. Equally as critical, for designers especially, is that these definitions of public space provide little guidance for creating successful public places. The paper’s author examines these definitions and the issues they pose and goes on to argue that what is needed is a new lexicon for addressing public space. Such a lexicon is briefly proposed. Such a lexicon, it is argued, would provide a more useful and broader discourse about what qualities define place and its political and spatial implications. In so doing it would also offer better guidance and insights for the design of social spaces.